Electrophile-Promoted Cyclization of Propargylic Amides - Bukšnaitienė, Rita; Čikotienė, Inga (Synlett, 2015)
Electrophilic cyclization of N-(3-arylprop-2-ynyl)amides to functionalized 4H-1,3-oxazines is described. It was found that the presence of an electron-rich aryl group next to the triple bond is crucial for a smooth and highly regioselective 6-endo-dig ring closure process.
Keywords: propargylic amides; electrophile; cyclization; oxazines; oxazolines